Groundwater Recharge Area Based on Hydrochemical and Environmental Isotopes Analysis in the South Bandung Volcanic Area - Rizka Maria; Satrio Satrio; Teuku Yan Waliyana Muda Iskandarsyah; Bombom Rachmat Suganda; Robert Mohammad Delinom; Dyah Marganingrum; Wahyu Purwoko; Dady Sukmayadi; Hendarmawan Hendarmawan (Universitas Gadjah Mada, 2021)
The determination of recharge areas needs to support the groundwater conservation in the southern volcanic Bandung area. This study aims to determine the recharge area based on environmental isotopes and hydrochemical. A sampling of 26 groundwater was carried out at springs, dug wells, and drilling wells. The variation in groundwater chemistry principally is controlled by a combination of ion exchange, silicate weathering, calcite, and dolomite dissolution of minerals. The hydrochemical facies were CaCl, CaMgCl, CaMgHCO3, CaHCO3, and NaKHCO3. The CaHCO3 facies describe moderate groundwater flows. The NaKHCO3 facies shows the mixing of shallow and deep groundwater. The recharge area in the central, proximal, and medial facies zone consists of 3 groups. Group I is considered water originating from local rainwater infiltration; Group II is considered the infiltration elevation which ranges from 980–1230 m asl; Group III estimated to be derived from the recharge elevation between 750–970 m asl, Group IV are more likely to show symptoms of evaporation or interaction with surface water. The discharge area is characterized by less active groundwater circulation, with dominant HCO3– and TDS value in the distal facies zone. Hydrochemical variation helped the identification of recharge areas in the volcanic facies.